Examining the relationship between children’s ADHD symptomatology and inadequate parenting: the role of household chaos - Wirth, Andrea; Reinelt, Tilman; Rauch, Wolfgang (Journal of attention disorders, 2019)
Objective: This study examines the interrelations of parenting practices, emotional climate, and household chaos in families with children with and without ADHD. In particular, indirect pathways from children’s ADHD symptomatology to inadequate parenting and negative emotional climate via household chaos were investigated. Method: Parenting, emotional climate, and household chaos were assessed using questionnaires and a speech sample of parents of 31 children with and 53 without ADHD, aged 7 to 13 years. Results: Group differences were found for certain parenting dimensions, the parent-child relationship, critical comments, and household chaos. While we found significant indirect effects between children’s ADHD and certain parenting dimensions through household chaos, no effects were found for any aspect of emotional climate. Conclusion: Children’s ADHD symptoms translate into inadequate parenting through household chaos, which underlines the need for interventions to improve household organization skills in parents of children with ADHD.